Multiferroic Bi 0.65 La 0.35 Fe 0.5 Sc 0.5 O 3 perovskite: magnetic and thermodynamic properties - Fertman, E.L. (2019)
Magnetic and thermodynamic properties of polycrystalline multiferroic Bi0.65La0.35Fe0.5Sc0.5O3 synthesized under high-pressure and high-temperature conditions are reported. Magnetic properties were studied using a SQUID magnetometer technique over the temperature range of 5−300 K in magnetic fields up to H=10 kOe. The field dependent magnetization M(H) was measured in magnetic fields up to 50 kOe at different temperatures up to 230 K after zero-field cooling procedure. A long-range magnetic ordering of the AFM type with a weak FM contribution occurs below the Néel temperature TN ~237 K. Magnetic hysteresis loops taken below TN show a huge coercive field up to Hc ~10 kOe. A strong effect of magnetic field on the magnetic properties of the compound has been found. Derivative of the initial magnetization curves demonstrates a temperature-dependent anomaly in fields of H=15−25 kOe. Besides, an anomaly of the temperature dependent zero-field cooled magnetization measured in magnetic fields of 6−7 kOe has been found. Origin of both anomalies is associated with inhomogeneous magnetic state of the compound. The heat capacity has been measured from 2 K up to room temperature and a significant contribution from the magnon excitations at low temperatures has been detected. From the low-temperature heat capacity, an anisotropy gap of the magnon modes of the order 3.7 meV and Debye temperature TD=189 K have been determined.